Analyzing Strategy of Character Building in Islamic Boarding Schools for College Students: A Comparative Case Study - Syaifulloh Yusuf; Marhumah Marhumah; Aziz Muslim (Universitas Muhammadiyah Malang, 2024)
This study explores the implementation of character education in Islamic boarding schools for university students, focusing on two specific institutions namely Kyai Haji Ahmad Dahlan Student Islamic Boarding School which is next called Persada UAD, and Surya Global Health College of Health Sciences Student Boarding School Yogyakarta which is called Pesantren STIKes Surya Global. The research employs a qualitative approach, utilizing interviews, observations, and document analysis involving several administrators from these boarding schools. The findings highlight the critical role of character education in shaping the morals and ethics of students, particularly their religious character. The presence of these Islamic boarding schools plays a significant role in reinforcing character values among students. The study identifies four key aspects of character education within these institutions: a clear and measurable vision, mission, and goals; an effective character education learning design; strict yet rational regulations for student conduct; and the practical application of character education values in daily student life. The research concludes that higher education institutions should integrate character education into both general and religious curricula, with Islamic boarding schools providing an ideal environment for this integration through a well-structured character education curriculum.